2014
DOI: 10.2478/s11686-014-0266-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic potentially pathogenic amoebae isolated from natural water bodies in Poland and their molecular characterization

Abstract: The free-living amoebae (FLA) may live in the environment and also within other organisms as parasites and then they are called amphizoic. They are potentially pathogenic for humans and animals and are found in water that is a source of infection. The aim of this study was molecular detection and identification of these FLA in natural water bodies in North-Western Poland to evaluate the risk of the pathogenic amoebae infections. We examined surface water samples collected from 50 sites and first, the tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The food availability for the growth of Acanthamoeba spp and the resistance of the cyst stage of these amoebae to chlorination, ozonation and filtration by biofilm formation, probably creates the potential for high distribution of Acanthamoeba spp in the aquatic environments (25,(37)(38)(39). Thus, this alarmingly frequency of this amoeba in water resources represents a significant hazard for the high risk populations, including the contact lens wearers and immunocompromised individuals [13,21,26].…”
Section: The Molecular Identificationmentioning
confidence: 99%
“…The food availability for the growth of Acanthamoeba spp and the resistance of the cyst stage of these amoebae to chlorination, ozonation and filtration by biofilm formation, probably creates the potential for high distribution of Acanthamoeba spp in the aquatic environments (25,(37)(38)(39). Thus, this alarmingly frequency of this amoeba in water resources represents a significant hazard for the high risk populations, including the contact lens wearers and immunocompromised individuals [13,21,26].…”
Section: The Molecular Identificationmentioning
confidence: 99%
“…Admittedly, the analysis of > 2,000‐bp fragments of the 18S rRNA gene accomplished in this study revealed that these two isolates, and nine other Polish isolates recently sequenced by Adamska et al. () and Leońska‐Duniec et al. () are the most similar to the T20 genotype, but in 2009 they in fact represented a new genotype.…”
Section: Discussionmentioning
confidence: 56%
“…(), as well as from natural (Adamska et al. ) and artificial (Leońska‐Duniec et al. ) water bodies were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations